ANALYSIS OF EXTERNAL AND INTERNAL FACTORS OF CORPORATE SOCIAL RESPONSIBILITY (CSR) IMPLEMENTATION IN IMPROVING COMMUNITY WELFARE - Wijaya, Septya Ari; Wiska, Mayroza; Gusteti, Yesi (Jurnal Ekonomi dan Bisnis Airlangga, 2022)
Introduction: CSR is very active role in overcoming the impact of the production process, as well as the welfare of the community around the company. This study wants to analyze the external and internal factors of CSR implementation in improving the welfare of the community by taking research at PT PLN (Persero) South Sumatra Generation Main Unit, Ombilin Generation Implementing Unit in Sijantang, Talawi District, Sawahlunto City, West Sumatra Province. Methods: This study uses quantitative methods with multiple linear regression analysis. A sample of 379 in this study was taken from three of the eleven villages in the Talawi sub-district of Sawahtulo city. The three villages are Salak Village, Sijantang Village, and Talawi Hili Village, due to the three villages received CSR funding from PLTU Ombilin. Data and questionnaires were distributed in April – June 2021. Results: Internal factors (primary measures and effectiveness) and external factors affect welfare in the implementation of CSR in Salak village, Sijantang village and Talawi Hili village at PT PLN (Persero), the Southern Sumatra generation main unit, the ombilin generation implementing unit. Conclusion and suggestion: A company in implementing its Corporate Social Responsibility (CSR) program must be serious about the interests of the community and the surrounding environment. In applying the concept of Corporate Social Responsibility (CSR), it can also be done jointly by inviting the government and community representatives to conceptualize the series of processes, start from program design or planning, program implementation, program monitoring, program evaluation up to reporting.